“Today let’s gently brush your ears”: ASMR som mediekulturelt og lydligt fænomen - Klausen, Helle Breth; Have, Iben (MedieKultur: Journal of media and communication research, 2019)
ASMR (Autonomous Sensory Meridian Response) is a physiological sensory reaction usually described as “a tingling, static-like sensation across the scalp, back of the neck and at times further areas in response to specific triggering audio and visual stimuli” (Barratt & Davis, 2015). In the last decade ASMR has also become a growing media cultural phenomenon, especially on YouTube, where ASMRtists create videos that help you overcome stress, loneliness and insomnia while making you feel good. This article follows a question raised by one of these ASMRtists concerning the ability of the videos to generate a feeling of human touch. In a combination of Media and Sound Studies, and supported by an empirical study of user comments on YouTube and Reddit, we argue that ASMR videos off er a social service by affording experiences of telepresence and pseudohaptic social audio-grooming and thereby meeting the ‘skin hunger’ of modern human beings.